Project politics, priorities and participation in rural water schemes - van Koppen, Barbara; Rojas, V.C.; Skielboe, T. (2012)
Governments, NGOs and financers invest considerable resources in rural domestic water supplies and irrigation development. However, elite capture and underuse, if not complete abandonment, are frequent. While the blame is often put on 'corrupt, lazy and indisciplined' communities, this article explores the question of how the public water sector itself contributes to this state of affairs. Four case studies, which are part of the research project Cooperation and Conflict in Local Water Governance, are examined: two domestic water supply projects (Mali, Vietnam); one participatory multiple use project (Zambia); and one large-scale irrigation project (Bolivia). It was found that accountability of water projects was upward and tended to lie in construction targets for single uses with already allocated funding. This rendered project implementers dependent upon the village elite for timely spending. Yet, the elite appeared hardly motivated to maintain communal schemes, unless they themselves benefited. The dependency of projects on the elite can be reduced by ensuring participatory and inclusive planning that meets the project's conditions before budget allocation. Although such approaches are common outside the water sector, a barrier in the water sector is that central public funds are negotiated by each sector by profiling unique expertise and single livelihood goals, which trickle down as single use silos. The article concludes with reflections on plausible benefits of participatory multiple use services for equity and sustainability.